Management of acute cholecystitis in UK hospitals: time for a change. Issue 943 (11th May 2004) - Cameron, I C; Chadwick, C; Phillips, J; Johnson, A G
Abstract : Early cholecystectomy for patients with acute cholecystitis is safe, cost effective, and leads to less time off work compared with delayed surgery. This study was designed to assess current practice in the management of acute cholecystitis in the UK. A postal questionnaire was sent to 440 consultant general surgeons to ascertain their current management of patients with acute cholecystitis. Replies were received from 308 consultants who were involved in treating patients with acute cholecystitis of whom 18 transferred these patients on to another team for further management the day after admission. Thirty two consultants (11%) routinely treated patients by early cholecystectomy, with limiting factors stated to be the availability of surgical staff, theatre space, and radiological investigations. The remaining consultants (n = 258) routinely manage their patients conservatively with intravenous antibiotics and allow the inflammation to resolve before undertaking cholecystectomy at a later date. Indications for undertaking early cholecystectomy during the first admission by this latter group included the presence of spreading peritonitis due to bile leak, empyema, and unexpected space on theatre list. The commonest method for both elective and early cholecystectomy is laparoscopic, but the percentage of consultants using an open method rises from 8% in the elective situation to 47% for urgent early cholecystectomy. Despite evidence which strongly advocates early cholecystectomy, this practice is routinely carried out by only 11% of consultants in the UK at present.